2012
DOI: 10.1037/a0027030
|View full text |Cite
|
Sign up to set email alerts
|

Media use, face-to-face communication, media multitasking, and social well-being among 8- to 12-year-old girls.

Abstract: An online survey of 3,461 North American girls ages 8-12 conducted in the summer of 2010 through Discovery Girls magazine examined the relationships between social well-being and young girls' media use--including video, video games, music listening, reading/homework, e-mailing/posting on social media sites, texting/instant messaging, and talking on phones/video chatting--and face-to-face communication. This study introduced both a more granular measure of media multitasking and a new comparative measure of med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
217
3
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(268 citation statements)
references
References 48 publications
24
217
3
7
Order By: Relevance
“…Firstly, daily multitasking most likely consists not only of dual-tasking in the classical sense but of a combination of divided attention, task switching and performing several automatized functions in parallel (Carrier et al, 2015). In fact, the media multitasking questionnaire used in the present as well as previous studies (Ophir et al, 2009;Pea et al, 2012) might not really tap into genuine multitasking. For example, "texting while doing homework" most likely means intermittently pausing while studying to write a text message, and not actually doing these two…”
Section: Behavioral Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…Firstly, daily multitasking most likely consists not only of dual-tasking in the classical sense but of a combination of divided attention, task switching and performing several automatized functions in parallel (Carrier et al, 2015). In fact, the media multitasking questionnaire used in the present as well as previous studies (Ophir et al, 2009;Pea et al, 2012) might not really tap into genuine multitasking. For example, "texting while doing homework" most likely means intermittently pausing while studying to write a text message, and not actually doing these two…”
Section: Behavioral Resultsmentioning
confidence: 79%
“…We used the shorter version of the media multitasking questionnaire (Ophir et al, 2009) adapted by Pea et al (2012) to create a media multitasking variable for each participant. The external validity of the resulting media multitasking questionnaire is yet to be firmly established, but several independent research groups have produced comparable indices for average media multitasking activity in their sample based on this questionnaire.…”
Section: Media Multitasking Scorementioning
confidence: 99%
See 2 more Smart Citations
“…There is empirical evidence that children between the ages of 8 and 12 years-a highly sensitive phase for identity formation, the development of social networks, and relationship building with peers who may serve as models and support-are negatively affected socio-emotionally by certain types of media use. A comprehensive study conducted with girls showed that high levels of media multitasking induce feelings of being less successful and not being normal, and reduced hours of sleep [12].…”
Section: The Social Dimension Of the Digital Revolution Is Not Yet Wementioning
confidence: 99%